Balneotherapy and rheumatoid arthritis: a randomized control trial - Santos, Isabel (2016)
Background: The effects of balneotherapy on rheumatoid arthritis (RA) are still controversial partly due to poor metho- dology used in randomized controlled trials, as reported in the international medical literature. Objectives: To determine whether spa therapy plus pharmacological treatment offers any benefit in the management of RA as compared to pharmacological treatment alone. methods: We conducted a prospective, controlled, unblinded randomly assigned study of patients with RA according to American College of Rheumatology criteria. Following the 2007recommendations of FRETH, the method designed for this study was “immediate treatment versus delayed treatment.” All patients were followed at the Oporto Hospital Centre and each physician observed the same patients throughout the study. Patients continued with their usual medications and maintained their daily life activities at home, at leisure and/or in the workplace. The spa therapy group received spa treatments for 21 days at S. Jorge Spa-Santa Maria da Feira. The main outcome measure was the HAQ-DI; the moderated regression analysis, together with the Johnson-Neyman technique, was used for statistical analysis. results: HAQ-DI at the end of treatment (21 days) and at the 3 month follow-up was improved in the spa group (odds ratio 0.37, confidence interval 0.09–0.64, P = 0.01 at 21 days, and 0.44, 0.15–0.72, P = 0.004 at 3 months). conclusions: In individuals in whom pain (physical and psychological) predominates, any complementary gain in function is beneficial. The main goal is to enhance quality of life.